Fibrin-I Degradation Products with a Molecular Weight Higher than That of Fibrinogen - von Hugo, René; Graeff, Henner (Thrombosis and Haemostasis, 1973)
The observation of intravascular lysis of fibrin deposits and of fibrinogen derivatives with a molecular weight higher than the parent molecule in human cases of disseminated intravascular coagulation (DIC) initiated the following in vitro study. Following streptokinase induced plasma clot solubilization fibrinogen derivatives were investigated after ß-alanine precipitation of the plasma samples by polyacrylamide (PAA) gel electrophoresis, intra gel immunoprecipitation, two dimensional gel electrophoresis and by agarose gel filtration. Three fibrin-i degradation products were observed and characterized according to their relative electrophoretic mobility in 5% PAA gel: 0.23, 0.35, 0.46 (fibrinogen: 0.43) x 10-5 cm2/V x sec. They could also be demonstrated after electrophoresis in the presence of 5 M urea. Agarose gel filtration yielded one peak at 180 ml of effluent volume. The 0.23 derivative was eluted in the peak fractions, whilst the 0.35 and 0.46 derivatives were eluted together at approximately 201 ml of the effluent volume (fibrinogen: 225 ml). This indicates, that the three fibrin-i degradation products described are molecular entities with molecular weights higher than fibrinogen and, that the 0.46 derivative has an increased charge/molecular size ratio in comparison with fibrinogen. Corresponding data were obtained by two dimensional gel electrophoresis in gels of different pore size.